2020
DOI: 10.1177/1363460720936464
|View full text |Cite
|
Sign up to set email alerts
|

Doing trust work – the purchase of sex in a Swedish context

Abstract: The relationship between commercial sex and intimacy has been in focus in a number of studies on the purchase of sex, often distinguishing between one-time visitors and regular customers. This article is based on a study exploring how men who buy sex as one-time visitors navigate between commercialization and intimacy in a Swedish context. Based on interviews with 29 Swedish men purchasing sex, an inductive thematic analysis has been applied. The findings show how the men in this study balance between exciteme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, street-based SFP is usually referred to by MWPWS in straightforward terms of strictly sexual experiences (Durant & Couch, 2019). Moreover, some MWPWS prefer to become regular clients of a specific woman, whom they pay for sex in indoor settings (Sanders, 2008)-while other MWPWS enjoy the rush and excitement of switching between multiple WPS at varying locations (Plantin, 2020).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…However, street-based SFP is usually referred to by MWPWS in straightforward terms of strictly sexual experiences (Durant & Couch, 2019). Moreover, some MWPWS prefer to become regular clients of a specific woman, whom they pay for sex in indoor settings (Sanders, 2008)-while other MWPWS enjoy the rush and excitement of switching between multiple WPS at varying locations (Plantin, 2020).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…Features such as communication, courtship rituals, sexual familiarity, and the desire for mutual satisfaction, as well as friendship and emotional connections can be important for regular purchasers (Milrod and Monto 2012;Sanders 2008a). However, the difference between regulars and one-time visitors is not clear-cut, and qualities presumed to be associated with regulars are also found among one-time visitors (Gr€ onvall, Holmstr€ om, and Plantin 2020;Jones and Hannem 2018). Trust and safety, for example, can be important both for men who purchase sex as regulars and as one-time visitors (Gr€ onvall, Holmstr€ om, and Plantin 2020;Sanders 2008b).…”
Section: The Purchase Of Sex and Intimacymentioning
confidence: 99%
“…However, the difference between regulars and one-time visitors is not clear-cut, and qualities presumed to be associated with regulars are also found among one-time visitors (Gr€ onvall, Holmstr€ om, and Plantin 2020;Jones and Hannem 2018). Trust and safety, for example, can be important both for men who purchase sex as regulars and as one-time visitors (Gr€ onvall, Holmstr€ om, and Plantin 2020;Sanders 2008b).…”
Section: The Purchase Of Sex and Intimacymentioning
confidence: 99%
“…However, the difference between regulars and one-time visitors is not clear-cut, and qualities presumed to be associated with regulars are also found among one-time visitors (Gr€ onvall, Holmstr€ om, and Plantin 2020; Jones and Hannem 2018). Trust and safety, for example, can be important both for men who purchase sex as regulars and as one-time visitors (Gr€ onvall, Holmstr€ om, and Plantin 2020;.…”
Section: The Purchase Of Sex and Intimacymentioning
confidence: 99%
“…Commercial sex is a phenomenon that involves several actors, and where interactions and perceptions of risk are interwoven on different levels . Previous research has shown that sex buyers are aware of or relate to the exploitation to which sellers are exposed, which affects their behaviour in different ways (Grönvall et al 2021a;. Men who purchase sex manage risk and make risk assessments when purchasing sex, Purchasing Sex in Sweden-A Risky Business • 397 both in relation to sellers and third parties.…”
Section: Introductionmentioning
confidence: 99%